Kazna zatvora u Srbiji – trendovi i odlike zatvoreničke populacije - Natalija Lukić (Revija za kriminologiju i krivično pravo)
The rate of persons deprived of liberty in Serbia has been increasing since 2006 and during the last decade this rate has been approximately 150. The data of the Council of Europe for the year 2022 show that in a large number of countries there a decrease in the rate of prisoners (all persons deprived of liberty) has been determined, and Serbia is still in the group of countries with a high rate of prisoners. However, the capacities of penal institutions in Serbia allow such figures, and according to the data, the total population of persons deprived of liberty is about 1000 people smaller than the maximum capacity allows. There is an average of 3.8 people in cells, while the European average is 2.1, and in half of the countries that number is 1.4. Similarly, the sentencing policy of the courts is uniform and the rate of those sentenced to prison generally follows the rate of all those convicted. In addition to a suspended sentence, the courts usually opt for a prison sentence. Taken together, imprisonment (including the house arrest that is enforced in the premises where the convicted person lives) amounts to about 1/3 of all imposed sanctions. The question arises why Serbia did not follow the trend of most European countries in which the population of persons deprived of their liberty has decreased in the last years? One of the explanations is the adoption of repressive criminal law solutions that in many situations limited the discretionary powers of judges in respect to penal sanctions. While on the one hand it is not in dispute that for serious crimes the only option will be a prison sentence, in the case of some incriminations it was better to leave the choice to the judges. However, it seems that the trend of transferring decision-making from the judiciary to the legislature is not typical only for Serbia (see for example: von Hirsch, 2017). At the same time, the public most often expresses repressive attitudes, which should be respected, but legal solutions should not be guided only by the interest of getting political support of voters but also by scientific and professional arguments. Scientific knowledge points to all the problems that, on the one hand, appear in prisons and how and in what way these problems prevent the successful execution of prison penalty and the implementation of treatment. In such situations, it would be more appropriate to opt for alternatives for less serious crimes, and in this way, prisoners could also receive greater commitment of treatment services as well as generally better conditions while serving their prison sentence. Although, according to statistical data, prisons are not overcrowded, it seems that those authors who claim that the frequency and length of prison sentences are primarily determined by existing capacities are right. If they are exceeded, one option is the construction of new institutions, which is usually associated with financial problems, and another option is amnesty and pardon. At the end, it should be borne in mind that long-term prison sentences are the least common, and that the largest number of prisoners will be released after a few years. It is clear that the public should also be interested in ensuring that at least some of them do not commit criminal acts again, and criminological research confirms that insisting on intimidation and retribution will not reduce recidivism rate.